1979
DOI: 10.1055/s-0028-1096279
|View full text |Cite
|
Sign up to set email alerts
|

Thymolipoma – A Rare, Benign Tumor of the Thymus Gland: Two Case Reports and Review of the Literature

Abstract: Two case reports of thymolipoma are presented. In a review of the literature on the subject, the clinical and etiologic features of this nonmalignant tumor in the anterior mediastinum are discussed. Although rare, thymolipoma should be considered in the differential diagnosis of mediastinal tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…15 Thymolipomas account for 2%-9% of all thymic neoplasms. [1][2][3] In the current series, 219 patients underwent thymectomy for different reasons over a period of 7 years, revealing thymolipomas in 4.1%. Thymolipomas often weigh more than 1 kg in young patients, as observed in patient #1 (2400 g).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…15 Thymolipomas account for 2%-9% of all thymic neoplasms. [1][2][3] In the current series, 219 patients underwent thymectomy for different reasons over a period of 7 years, revealing thymolipomas in 4.1%. Thymolipomas often weigh more than 1 kg in young patients, as observed in patient #1 (2400 g).…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3] The tumor is characterized by slow, encapsulated growth with no tendency to recur after a complete surgical excision. As thymomas, thymolipomas are sometimes associated with myasthenia gravis, aplastic anemia, hypogammaglobulinemia, lichen planus, and Graves' disease.…”
Section: Introductionmentioning
confidence: 99%
“…Ringe et al . reported that half of patients with thymolipoma were asymptomatic, and most cases were coincidentally found to have cardiomegaly on chest X‐ray . The patients are often asymptomatic despite the tumor's growth, as this tumor is slowly progressive.…”
Section: Discussionmentioning
confidence: 99%
“…As for thymic hyperplasia, the adipose tissue is not observed as extensively as that in thymolipoma (4,8).…”
mentioning
confidence: 99%
“…Microscopic evaluation reveals broad mature adipose tissue areas in conjunction with thymic tissues islets of varying amounts. Calcification and cystic degeneration are evident in Hassal's corpuscles in a majority of the cases (4,8). It should be differentiated histopathologically from lipoma, well-differentiated liposarcoma and thymic hyperplasia.…”
mentioning
confidence: 99%